2019
DOI: 10.1044/2019_ajslp-18-0155
|View full text |Cite
|
Sign up to set email alerts
|

Communicative Use of Triadic Eye Gaze in Children With Down Syndrome, Autism Spectrum Disorder, and Other Intellectual and Developmental Disabilities

Abstract: Purpose This study examines differences in the communicative use of triadic eye gaze (TEG) during a communicative interaction in 2 neurodevelopmental disorders: Down syndrome (DS) and autism spectrum disorders (ASD), and a 3rd group of varying disabilities associated with intellectual and developmental disabilities (IDDs). Also, the relationship between TEG use and language abilities was explored. Method Participants were 45 children, 15 in each group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
(84 reference statements)
1
3
0
2
Order By: Relevance
“…Consistent with previous work (Murillo et al, 2021), the two groups of autistic children with different CCDI (Time 2) levels produced similar total prelinguistic communicative behaviours in our study. We are not surprised that autistic children demonstrated low frequencies of single and multimodal eye gaze communicative behaviours because previous studies have also described this outcome (Hahn et al, 2019;Murillo et al, 2021). We also found that single gestures were the most fre-quent of all communication behaviours in the low CCDI group, and the two groups used similar amounts of single gestures.…”
Section: Gesture and Vocalisation Combinations Uniquely Predict Expre...supporting
confidence: 76%
See 2 more Smart Citations
“…Consistent with previous work (Murillo et al, 2021), the two groups of autistic children with different CCDI (Time 2) levels produced similar total prelinguistic communicative behaviours in our study. We are not surprised that autistic children demonstrated low frequencies of single and multimodal eye gaze communicative behaviours because previous studies have also described this outcome (Hahn et al, 2019;Murillo et al, 2021). We also found that single gestures were the most fre-quent of all communication behaviours in the low CCDI group, and the two groups used similar amounts of single gestures.…”
Section: Gesture and Vocalisation Combinations Uniquely Predict Expre...supporting
confidence: 76%
“…We are not surprised that autistic children demonstrated low frequencies of single and multimodal eye gaze communicative behaviours because previous studies have also described this outcome (Hahn et al., 2019; Murillo et al., 2021). We also found that single gestures were the most frequent of all communication behaviours in the low CCDI group, and the two groups used similar amounts of single gestures.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…These findings, that is concurrent relationships at Time 2, align with the view that the dynamic process of joint engagement supports language development ( Bakeman and Adamson, 1984 ; Adamson et al, 2004 ; Paparella and Kasari, 2004 ; Bottema-Beutel et al, 2014 ). Further, the association between joint engagement and receptive and expressive language abilities in DS is echoed in prior research on joint attention—which is similar to joint engagement—and related supportive skills, like triadic eye gaze, ( Mundy et al, 1995 ; Harris et al, 1996 ; Seager et al, 2018 ; Hahn et al, 2019 ). Thus, targeting joint engagement may be especially helpful for language interventions for children with DS into the second year.…”
Section: Discussionmentioning
confidence: 89%
“…Ia berinteraksi dengan orang lain melalui gerakan tubuhan dan tatapan mata. Namun pada beberapa kasus, terapi atau perlakuan terhadap penderit DS terkait kemampuan verbal sudah mulai dilakukan meski masih banyak kendala yang dtiemukan namun ini untuk mengantisipasi mereka dari keterbatasan komunikasi dengan lingkungan [21]. Karna umumnya penderita DS yang kesulitan menyampaikan pesan secara verbal akan mengalami peningkatan dan ketidakstabilan emosi [22].…”
Section: Definisi Operasionalunclassified